“Potência do pensamento – Schopenhauer e o mundo contemporâneo” - Sanvitto, Paulo Cesar (2022)
This paper aims to assess the actuality of Schopenhauer's thought, expressed in several concepts, developed especially in the first half of the 19th century, and its relation to what is experienced in contemporary times. Amongst the sophisticated themes deeply studied by the thinker, we will give a special emphasis to the Will and Representation, which titles his magnum opus, and also to the Will as a thing-in-itself, Will to life, Death, and Freedom of the Will. Among several and unnerving world problems linked to the powerful thought of the Frankfurt philosopher, we will focus mainly on Fascism: yesterday, today, eternal?, title of the third chapter, and Memories that evanesce spontaneously or premeditatedly, which names the fourth chapter. We have checked works by several authors in order to constitute the texts, with the aim of presenting themes under different points of view: philosophical, historical, sociological, and psychoanalytic. The fifth chapter, entitled Will in Schopenhauer and its meaning today, was focused almost exclusively on Schopenhauer's thought. Perhaps, it is a search for possibilities to elevate the will to life over death temptations that permeate many contemporary thoughts, as well as to keep alive individual and collective memories of great catastrophes, wars, and genocides, with full understanding of their meanings for, thus, preventing their often almost inevitable comeback.